The Nimodipine-Sparing Effect of Perioperative Dexmedetomidine Infusion During Aneurysmal Subarachnoid Hemorrhage: A Prospective, Randomized, Controlled Trial - Ren, Chunguang; Gao, Jian; Xu, Guang jun; Xu, Huiying; Liu, Guoying; Liu, Lei; Zhang, Liyong; Cao, Jun-Li; Zhang, Zongwang (Frontiers in Pharmacology, 2019)
Background: The reduction of blood pressure after long-term intravenous administration of nimodipine has been associated with neurological deterioration. This prospective, randomized, controlled trial was performed to evaluate the nimodipine-sparing effect of perioperative dexmedetomidine infusion during aneurysmal subarachnoid hemorrhage. Methods: One hundred and nine patients were divided into three groups. The primary outcome measure was the total consumption of nimodipine during the first 48 h after surgery. The secondary outcome measures were recovery time at PACU, postoperative pain intensity scores, dexmedetomidine and sufentanil consumption, hemodynamic, satisfaction of patients and neurosurgeon, neurologic examination, Bruggemann comfort scale, and adverse effects.We also recorded the incidence of symptomatic cerebral vasospasm, Glasgow Outcome Score and incidence of cerebral infarction. Results: The consumption of nimodipine during the first 48 h after surgery was significantly lower in Group D2 (P < 0.05). Compared with Group C, HR and MAP were significantly decreased from T2 to T12 in Group D1 and D2 (P < 0.05). Patients in Group D2 showed a significantly decreased MAP from T5 to T9 compared with Group D1 (P < 0.05). The consumption of sevoflurane, remifentanil, dexmedetomidine, and nimodipine were all significantly reduced in Group D1 and D2 during surgery (P < 0.05). Compared with Group C, MAP was significantly decreased in Group D1 and D2 during the first 48 h after surgery (P < 0.05). Compared with Group C, consumption of sufentanil and dexmedetomidine at 1 h, pain intensity at 1 h and 8 h after surgery were significantly decreased in Group D1 and D2 (P < 0.05). FAS was significantly higher in Group D2 at 8 h, 16 h, and 24 h after surgery. LOS was significantly lower only in Group D2 at 0.5 h after surgery (P < 0.05). Compared with Group C, BCS was significantly higher Group D2 at 4 h and 8 h after surgery (P < 0.05). Conclusions: Dexmedetomidine significantly reduced the total consumption of nimodipine during the first 48 h after surgery and promoted early rehabilitation of patients although the incidence of symptomatic cerebral vasospasm, GOS, and cerebral infarction were not reduced.